Effect of treatment with salicylic acid solution on the quality of cherry fruit after storage - Василишина, О. В. (Scientific Progress & Innovations, 2018)
Cherry is fruit with a short shelf life of only 15 days at the temperature of 0 °С. Every year about 20% of product losses are due to the lack of appropriate measures for primary processing and storage of products. Salicylic acid plays an important role in a wide range of physiological and metabolic reactions, including delayed maturation, by delaying the synthesis of ethylene and reducing the physiological diseases of the fruit. However, the effect of treatment with salicylic acid on cherry fruits and their physiological and biochemical parameters has not been investigated. Therefore, the purpose of our work was to study the effect of pre-treatment with salicylic acid solution on the chemical composition of cherry fruit. For this purpose, the day before harvesting with the cherry varieties of Shpanka and Lotivka of the yield of the year 2016−2017 were sprayed the aqueous solution of 50 mg/l or 100 mg/l of salicylic acid. They were dried by natural way. After 24 hours, the fruit of typical colour and shape were taken from the tree, placed in boxes of 5 to 5 kg each, according to the guidelines for the storage of fruit, vegetables, and grapes. We preserved them in the conditions of the refrigerating chambers of the department of the technology of storage and processing of fruit and vegetables at the temperature of 5±0,5°С and relative humidity of 95±1%. The options were the following: control − unprocessed fruit and cherry fruit treated with a solution of 50 mg/l or 100 mg/l of salicylic acid. The processing of cherry fruit with a solution of salicylic acid allowed to extend the shelf life to 21 days. The most effective treatment was 100 mg/l solution of salicylic acid. Natural mass losses in this case are 4.9−5.1 %, losses in the content of dry soluble substances 5.3−6.6%, acids 12.3−9%, the losses of ascorbic acid are reduced in 1.3−1.1 times. As the results of the correlation analysis showed, the level of natural mass losses strongly is correlated with the content of ascorbic acid (r = -0.65) and titrated acids (r = -0.57). The weight loss factor has the greatest influence on the type of treatment (85.6%).